Antioxidant Activity of Ethanol Extract of Chinese Petai Peel (Leucaena leucocephala (Lam.) de Wit) Using DPPH (1,1-diphenil-2-picrylhydrazyl) Method - Rahmayanti, Putri; Ridwanto, Ridwanto (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2023)
The Chinese petai plant (Leucaena leucocephala (Lam.) de Wit) has been used in various systems of traditional medicine for the treatment of various diseases in humans. The Chinese petai plant (Leucaena leucocephala (Lam.) de Wit) contains antioxidant secondary metabolites that can inhibit oxidation reactions by binding to free radicals and highly reactive molecules. The purpose of this study was to determine the class of chemical compounds contained in the ethanol extract of Chinese petai peel and the antioxidant activity of the ethanol extract of Chinese petai peel (EEKPC). The stages of this research included: collection and processing of simplicia; preparation of the extract by maceration with 70% ethanol; characterization test of simplicia powder; phytochemical screening of ethanol extract of petai cina; antioxidant activity test of EEKPC using the DPPH (1,1-diphenyl-2-pikrilhidrazyl) free radical scavenging method using UV-Vis spectrophotometry at a wavelength of 516 nm. The results of the phytochemical screening examination of Chinese Petai Peel Ethanol Extract (EEKPC) contained alkaloids, flavonoids, saponins, tannins, and triterpenoids. The results of measuring the antioxidant activity of EEKPC showed strength in the "strong" category with an IC50 value of 91.0189 μg/ml.